Brazil Low Carbon Case Study : Land Use, Land-Use Change, and Forestry - World Bank (Washington, DC, 2013)
This report presents the partial results related to land use, land-use change and the forestry sector from a larger multisectoral low-carbon study for Brazil. Since the 1992 Kyoto Accord, Brazil has been committed to reducing its carbon emissions. The overall aim of this study was to support Brazil's efforts to identify opportunities to reduce its emissions in ways that foster economic development. The primary objective was to provide the Brazilian government with the technical inputs needed to assess the potential and conditions for low-carbon development in key emitting sectors. To this end, the World Bank study adopted a programmatic approach in line with the Brazilian government's long-term development objectives. These are: to anticipate the future evolution of Brazil's emissions to establish a Reference Scenario; identify and quantify lower carbon-intensive options to mitigate emissions, as well as potential options for carbon uptake; assess the costs of these low-carbon options, identify barriers to their adoption, and explore measures to overcome them; and build a low-carbon emissions scenario that meets the same development expectations. The study also analyzed the macroeconomic effects of shifting from the Reference Scenario to the low-carbon one and the financing required. Reference-scenario results for these main areas show that deforestation remains the key driver of Brazil's future emissions through 2030. The study evaluated the mitigation and carbon uptake options, assessing all the relevant sub-sectors for each sector; determined the viability of the options investigated; and finally, constructed low-carbon scenarios for each sector to assist them lowering their greenhous gas (GHG) carbon emissions.